2021
DOI: 10.3390/ijerph18178933
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of Apprentices during the COVID-19 Pandemic in Austria and the Effect of Gender, Migration Background, and Work Situation

Abstract: This study assessed the mental health of apprentices during the COVID-19 pandemic in Austria and the effect of gender, migration background, work situation, and work sector. An online survey via REDCap was performed with a sample of 1442 apprentices (female: 53.5%, male: 45.4%, diverse: 1.1%, migration background: 28.4%) from 29 March to 18 May 2021. Indicators of mental health were depression (PHQ-9), anxiety (GAD-7), well-being (WHO-5), disordered eating (EAT-8), and insomnia (ISI-7). There was a high preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
3
22
0
2
Order By: Relevance
“…In fact, migrant women, especially young women, have the highest unemployment rate in Spain ( 18 ). Consistent with other studies, poor living conditions due to low-income levels may have made it harder to respect curfews or work from home ( 59 ). Hegemonic structure such as immigration law affects people, especially in employment systems, as well as through government policies and actions ( 5 , 60 ).…”
Section: Discussionsupporting
confidence: 89%
“…In fact, migrant women, especially young women, have the highest unemployment rate in Spain ( 18 ). Consistent with other studies, poor living conditions due to low-income levels may have made it harder to respect curfews or work from home ( 59 ). Hegemonic structure such as immigration law affects people, especially in employment systems, as well as through government policies and actions ( 5 , 60 ).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, other studies, for example, from China and Austria, did not find an independent industry effect on employee mental health. 34 , 35 These opposing results might be due to the different national circumstances and suggest that differences in mental health might be due to the specific work situation rather than the industry. Furthermore, this study showed an increase in MD over the course of the pandemic, so the timing of a survey should always be considered when comparing different studies.…”
Section: Discussionmentioning
confidence: 99%
“…We chose these variables because previous research indicated that gender and migration background significantly impact adolescents’ mental health [ 22 , 23 , 24 ]. Dale et al [ 25 ] showed that apprentices have worse mental health than high school students. For this reason, we excluded respondents who reported being apprentices, not attending a school at all, or doing something else, thereby focusing on young people attending compulsory school or some form of secondary school.…”
Section: Methodsmentioning
confidence: 99%